Study of Changes in Serum Calcium Level during Postmenopausal Period of Women in Bangladesh - Nargis, Susmita; Bhuyan, Rasel; Roy, Heera Lal; Mahmudul Hasan, Kazi Muhammad; Chakraborty, Pijush Kumar (Medicine Today, 2022)
Introduction: The study was designed to evaluate the serum calcium levels may be altered in postmenopausal women. Materials and Methods: This case control study was carried out in the Department of the Biochemistry, Mymensingh Medical College, Mymensingh, from January 2015 to December 2015. The subjects were selected on the basis of inclusion and exclusion criteria by purposive (non-random) method. This study included 50 postmenopausal women as case. Results: The results were compared with 50 apparently healthy premenopausal women as control. All statistical analysis was done by SPSS windows package. The values were expressed as Mean ± SD. Statistical significance of difference between two groups were evaluated by using student’s unpaired t-test. Serum calcium level was analyzed. Serum calcium was determined by using colorimetric method. The mean value of serum calcium was 8.59±1.02 (mg/dl) respectively in group B (Case) and 6.36 ± 1.06 (mg/dl ) in group A(Control). The levels of serum calcium was significantly decreased in group B. Conclusion: Menopause has an effect on serum calcium which leads to increased risk of development of osteoporosis. The present study may facilitated the clinicians and gynecologists to update their knowledge in regard to serum calcium level of women associated with menopause. Medicine Today 2022 Vol.34(2): 150-152